Differences in performance indicators between winning and losing teams in the UEFA Champions League - Lago-Penas, C.; Lago-Ballesteros, J.; Rey, E. (Journal of Human Kinetics, 2011)
The aim of the present study was to identify performance indicators that discriminate winning teams from drawing and losing teams in the UEFA Champions League. All 288 matches played at the group stage in the 2007-2008, 2008-2009, and 2009-2010 seasons were analyzed. The game-related statistics gathered were: total shots, shots on goal, effectiveness, passes, successful passes, crosses, offsides committed and received, corners, ball possession, crosses against, fouls committed and received, corners against, yellow and red cards, venue, and quality of opposition. Data were analyzed performing a one-way ANOVA and a discriminant analysis. The results showed that winning teams had significantly higher average values that were for the following game statistics: total shots (p<0.01), shots on goal (p<0.01), effectiveness (p<0.01), passes (p<0.05), successful passes (p<0.05), and ball possession (p<0.05). Losing teams had significantly higher values in the variable yellow cards (p<0.01), and red cards (p<0.01). Discriminant analysis allowed to conclude the following: the variables that discriminate between winning, drawing and losing teams were the shots on goal, crosses, ball possession, venue and quality of opposition. Coaches and players should be aware of these different profiles in order to increase knowledge about game cognitive and motor solicitation and, therefore, to design and evaluate practices and competitions for soccer peak performance teams in a collective way.